2022
DOI: 10.25134/erjee.v10i3.6470
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Project-Based Learning for Efl Students’ Writing Achievement at Tertiary Level

Abstract: Writing is the process of recursively producing written work. This study aims to explore the effectiveness of project-based learning to elevate the students’ academic writing at the tertiary level and to know the students’ opinion of the implementation of project-based learning in teaching writing. A mixed method design is employed and it is conducted in twelve sessions. It involves thirty- eight students of the English Department of a private university in Mataram West Lombok, Indonesia who attend academic wr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…The present study provides evidence for the effectiveness of using hybrid Project-based learning approach in developing English major student teachers" 21 st Century Skills, academic achievement and their positive attitudes towards PBL. The findings of the current study corroborate the previous relevant studies that investigated the effect of using PBL approach in general on developing language skills such as writing as proved by Thitivesa and Essien (2013), Giawa (2022), Ilham (2022); EFL productive skills such as Rochmahwati (2016), andAstawa, Artini andNitiasih (2017); and language proficiency improvement in general such as Imtiaz and Asif (2012), Arabloo et al (2021), andYaprak (2022). Moreover, it substantiates the results reached by other similar studies that PBL had a significant effect on improvement of 21st century skills (4Cs) such as Vicheanpant andRuenglertpanyakul (2012), Bani-Hamad andAbdullah (2019), Badr (2021), Haniah et al (2021), Sari and Prasetyo (2021), and Al-Bahadli et al (2023.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The present study provides evidence for the effectiveness of using hybrid Project-based learning approach in developing English major student teachers" 21 st Century Skills, academic achievement and their positive attitudes towards PBL. The findings of the current study corroborate the previous relevant studies that investigated the effect of using PBL approach in general on developing language skills such as writing as proved by Thitivesa and Essien (2013), Giawa (2022), Ilham (2022); EFL productive skills such as Rochmahwati (2016), andAstawa, Artini andNitiasih (2017); and language proficiency improvement in general such as Imtiaz and Asif (2012), Arabloo et al (2021), andYaprak (2022). Moreover, it substantiates the results reached by other similar studies that PBL had a significant effect on improvement of 21st century skills (4Cs) such as Vicheanpant andRuenglertpanyakul (2012), Bani-Hamad andAbdullah (2019), Badr (2021), Haniah et al (2021), Sari and Prasetyo (2021), and Al-Bahadli et al (2023.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have revealed project-based instruction as being capable of providing English language learners with prospects for comprehensible output and integrated language learning. For instance, PBL proved to be effective in enhancing EFL writing skills (Thitivesa& Essien, 2013;Giawa, 2022;Ilham, 2022), EFL productive skills (Astawa, Artini & Nitiasih, 2017), and language proficiency improvement in general (Arabloo et al, 2021;Yaprak, 2022). Moreover, PBL has a significant effect on improvement of 21st century skills (4Cs) among secondary school students (Bani-Hamad& Abdullah, 2019;Badr, 2021;Haniah et al, 2021;Sari& Prasetyo, 2021).…”
Section: Generation Zmentioning
confidence: 99%
“…Increasing students' adversity quotient (Mardiana & Amalia, 2022). Several researchers have also proven the impact of project-based learning, such as students feeling challenged, motivated, and more critical when given writing assignments in the form of projects (Ilham, 2022;Komang Sri Wardani et al, 2021;Maya Sari et al, 2023). Free project output also increases students' creativity in creating (Yamin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%